Dödshjälpens vara eller inte vara? En undersökning om patientens rätt till självbestämmande kan motivera tvingande legalisering av dödshjälp i Sverige - Wahlström,Alexander (2024)
The purpose of this essay is to examine if a patient’s right to autonomy according to Swedish and European law can encourage compulsory legislation of euthanasia. The research question addresses the limit of a patients right to autonomy in the end of his/her life and what that limit means for the legislation. The method used is the legal dogmatic method with a critical approach to applicable law to examine the limit of a patient’s right to autonomy. The theoretical foundation is that the patient has a right to autonomy throughout his/her whole life. A liberal legal theory for the essay furthermore means that everything that doesn’t hurt anyone shouldn’t be prohibited. Consequently, this means that what isn’t prohibited in a legal system shouldn’t be prohibited un-less it’s strongly suggested otherwise. The main part of the essay begins by defining euthanasia before establishing relevant law. The study continues by examining the limit of established law through a study of the Swedish consent laws as well as a study of cases from The European Court of Human Rights. The conclusion is that applicable law on the area can’t encourage compulsory legislation of euthanasia. The European Court of Human Rights caselaw emphasizes that art. 2 doesn’t have to conflict with legislation for euthanasia or art. 8 if safeguards exist to protected vulnerable groups. The fact that the convention is a living instrument and shall be interpreted in the light of present-day society haven’t made it possible to demand euthanasia as an individual right, but such interpretation of art. 8 is possible in accordance with caselaw. States enjoy a wide margin of appreciation regarding euthanasia. The limit of a patient’s right to autonomy according to the Swedish laws on consent is when a patient demand help in ending his/her life. Swedish law prioritizes palliative care and the latest caselaw even emphasizes that it’s a basic requirement for a right to a dignified death. The National Board of Health in Sweden points out several flaws in its palliative care which should indicate the need for improvements to achieve fundamental human freedoms and rights. The flaws should be followed by a study into legislation of euthanasia. Especially since there is a positive trend on euthanasia in Europe.
Keywords: Socialrätt; Medicinsk rätt; Dödshjälp; EKMR